The crustacean Armadillidium vulgare (Latreille, 1804) (Isopoda: Oniscoidea), a new promising model for the study of cellular senescence. Issue 2 (19th February 2020) - Depeux, Charlotte; Samba-Louaka, Ascel; Becking, Thomas; Braquart-Varnier, Christine; Moreau, Jérôme; Lemaître, Jean-François; Laverre, Tiffany; Paulhac, Hélène; Dechaume-Moncharmont, François-Xavier; Gaillard, Jean-Michel; Beltran-Bech, Sophie
Abstract: Senescence, the decline of physiological parameters with increasing age, is a quasi-ubiquitous phenomenon in the living world. The observed patterns of senescence, however, can markedly differ across species and populations, between sexes, and even among individuals. To identify the drivers of this variation in senescence, experimental approaches are essential and involve the development of tools and new study models. Current knowledge of the senescence process is mostly based on studies on vertebrates and the main information about senescence in invertebrates is mostly limited to model organisms such as Caenorhabditis elegans or Drosophila melanogaster . In this context, we tested whether biomarkers of vertebrate ageing could be used to study senescence in a new invertebrate model: the common woodlouse Armadillidium vulgare (Latreille, 1804). More specifically, we looked for the effect of age in woodlouse on three well-established physiological biomarkers of ageing in vertebrates: immune cells (cell size, density, and viability), β-galactosidase activity, and the gene expression of telomerase reverse transcriptase (TERT), an essential subunit of telomerase protein. We found that the size of immune cells was higher in older individuals, whereas their density and viability decreased, and that the β-galactosidase activity increased with age, whereas the TERT gene expression decreased. These findings demonstrate that woodlouse displays age-related changes in biomarkers of vertebrate senescence, with different patterns depending on gender. The tools used in studies of vertebrate senescence can thus be successfully used in studies of senescence of invertebrates such as the woodlouse. The application of commonly used tools to new biological models offers a promising approach to assess the diversity of senescence patterns across the tree of life.